Efficacy and safety of conversion from cyclosporine to everolimus in living‐donor kidney transplant recipients: an analysis from the ZEUS study. (20th August 2014) - Lehner, Frank; Budde, Klemens; Zeier, Martin; Wüthrich, Rudolf P.; Reinke, Petra; Eisenberger, Ute; Mühlfeld, Anja; Arns, Wolfgang; Stahl, Rolf; Heller, Katharina; Witzke, Oliver; Wolters, Heiner H.; et al.
Summary Conversion of living‐donor kidney transplant patients from calcineurin inhibitor therapy to an mTOR inhibitor is poorly documented. In the prospective, multicentre ZEUS study, 300 kidney transplant recipients without prior rejection (Banff grade >1) and serum creatinine ≤265 μmol/l were randomized to continue cyclosporine or convert to everolimus at 4.5 months post‐transplant. In a post hoc analysis of 80 living‐donor recipients, adjusted estimated GFR (Nankivell) at month 12 (the primary endpoint) was 74.3 (95% CI [70.7, 77.9]) ml/min/1.73 m2 with everolimus versus 63.8 (95% CI [60.0, 67.7]) ml/min/1.73 m2) with cyclosporine, a difference of 10.5 ml/min/1.73 m2 in favour of everolimus (P < 0.001). From randomization to month 12, adjusted estimated GFR increased by a mean of 9.8 (95% CI [6.2, 13.4]) ml/min/1.73 m2 with everolimus versus −0.7 (95% CI [−4.6, 3.1]) ml/min/1.73 m2) (P < 0.001) with cyclosporine. There were six biopsy‐proven acute rejection episodes in everolimus‐treated patients (five Banff grade I) and one episode in cyclosporine‐treated patients (Banff grade 1). Overall safety profile was similar between groups. Discontinuation due to adverse events occurred in three everolimus patients (7.1%) and five cyclosporine patients (13.2%) between randomization and month 12. Initiation of everolimus with early elimination of calcineurin therapy is associated with a significant renal benefit at 12 months post‐transplant that is observed in both living and deceased‐donor recipients. (clinicaltrials.gov NCT00154310)